A Study on the Lateral Distribution of Cherenkov Radiation of Extensive Air Showers at High Observation Levels - Davoud Purmohammad (Iranian Journal of Astronomy and Astrophysics)
By using CORSIKA code, for simulation of extensive air showers for observation levels at different altitudes, the variation of the lateral distribution of Cherenkov radiation of showers with altitude is studied. The lateral distribution function introduced by Tunka experiment group has been examined for 13 observation levels. The possibility of estimating the maximum depth of showers, using the steepness of the lateral distribution of Cherenkov radiation at different observation levels is investigated. It is shown that the relationship between the steepness of the lateral distribution of Cherenkov radiation and the maximum depth of showers, which was introduced in previous researches, should be calibrated for each observation level separately. An evaluation for errors in shower maximum depths estimated by this method, for an observation level at 4000 meters above the sea level is provided as an example. The errors in the estimated shower maximums are larger than the corresponding errors in the atmospheric fluorescence technique.